Effect of Low-Level LASER Therapy on Wound Recovery and Sequelae After Orthognathic Surgery: A Randomized Controlled Trial - Alireza Sadighi; Hasan Momeni; Amir Mansour Shirani (Wolters Kluwer Medknow Publications, 2019)
Introduction: Despite the application of low-level laser therapy (LLLT) in diverse dental procedures, its postoperative effects especially on wound recovery after orthognathic surgery have not been well explored. Therefore, the current study aimed to investigate the effects of 660 nm LLLT on postoperative consequences of orthognathic surgery through a randomized controlled trial. Material and Methods: In this split-mouth, triple-blind randomized controlled trial, 12 patients who needed bimaxillary orthognathic surgery were recruited. After the surgery, one side of their face was irradiated with a diode low-level laser device of 660 nm during 1, 2, 4, and 7 days after the surgery, and the other side of their face was considered as placebo. Later, LLLT outcomes were assessed in terms of swelling, pain, and wound recovery after the surgery. For estimating the swelling, distances between tragicus to corner of mouth, tragicus to pogonion, and gonion to cantus were measured; for pain evaluation, the visual analog scale was used. Recovery of wounds was assessed via two ways of probing wounds depth and appraising their clinical features. Results: Although both LLLT and placebo sides presented a constant reduction of swelling over three postoperative months, the swelling in LLLT sides was significantly lower than placebos during the second and fourth days after the surgery. Regarding the pain, there were no significant differences on either sides of the face, 4 days after the surgery. Wounds probing indicated better recoveries at LLLT sides for both upper and lower jaws, whereas the results of clinical features did not show any significant differences between LLLT and placebo sides. Conclusion: LLLT can effectively accelerate the wound recovery after an orthognathic surgery. Also, it is helpful for postoperative sequelae of orthognathic surgery including swelling and pain.